Antifungal activity of Trichoderma VOCs against Pyrenophora teres, the causal agent of barley net blotch - Moya, Paulina (2018)
Many species of Trichoderma produce secondary metabolites such as volatile organic compounds (VOCs) that reduce plant diseases and promote their growth. In this work we evaluated the antagonistic effects of VOCs released by eight strains of two Trichoderma species against Pyrenophora teres Drechsler, the causal agent of barley net blotch. Antagonism was estimated based on the percentage of mycelial growth inhibition according to the confronted cultures method. VOCs extraction and identification were performed by gas chromatography and mass spectrometry, through different methodologies for VOCs emitted by antagonists and pathogens alone or when confronted. VOCs produced by all Trichoderma strains inhibited mycelial growth of the pathogen in a range of 3 to 32%, showing weak and unpigmented mycelia with vacuolization. In addition, P. teres stimulated the release of VOCs by both Trichoderma species. The major groups of VOCs detected were sesquiterpenes, followed by diterpenes, terpenoids and eight-carbon compounds. This is the first report about characterization of volatiles emitted by Trichoderma in the presence of P. teres.